Basic Online Pennsylvania Legal Research for Librarians - Laura J. Ax-Fultz (Pennsylvania Libraries: Research & Practice, 2014)
Librarians engage in reference interviews where knowledge of legal research is necessary, but they may not have formal training in legal research. Understanding a few basic elements of legal research will create a foundation of knowledge from which librarians can learn to effectively help patrons locate legal resources. The author presents these elements and describes their application in the context of researching free online Pennsylvania legal resources, including special advice to clarify the librarian’s role when working with patrons who are conducting legal research. The author also discusses the value of librarians creating a toolkit of free online Pennsylvania resources.